Audiência de custódia e medidas cautelares pessoais no Estado Democrático de Direito - Camargo, Rodrigo Tellini de Aguirre (2019)
The present work deals with the contextualization of the "custody hearing" in the Brazilian Criminal Procedure model as an instrument for effecting the fundamental right of prompt judicial presentation of prisoners, provided for in article 7, item 5, of the American Convention on Human Rights. São José da Costa Rica), its procedural conformation by Resolution 213/15 of the National Council of Justice and adaptation of the system of precautionary measures. We will deal with social inclusion measures within the custody hearings and restorative justice measures as an alternative to solving the criminal case. We will analyze the pilot project of the National Council of Justice, presenting statistical data. Finally, we will reinforce the humanistic advantages of personal prison control